(untitled) (Pulse, 2015)
Objectives: To determine the health seeking behaviour of mothers / care givers of children under 5 years of age during their illnesses. Materials and methods: A descriptive cross-sectional study was conducted among 439 mothers/ care givers of under 5 year old children in an urban slum area of Dhaka city from September 2013 to February 2014. Data were collected through face-to-face interview by using a structured pre-tested questionnaire. The collected data were analyzed using SPSS version 20.0. All analyzed data were presented in the form of percentages. Chi-square test was applied wherever applicable. Results: Out of 439 mothers / care givers, most (90%) of them sought health care services during their childrens illness. [A statistically significant association was found between mothers /care givers education and sought health care services during illness of children (p=0.055). In the study, 200 (50%) of the respondents consulted drug sellers of medicine shops during their childrens illness. Others went to medical college hospital (34.6%), Government hospitals (13.5%), consulted a private practitioners (11%) and NGO facilities (6.3%). Forty (9.1%) respondents did not seek any health care with multiple reasons or responses. Majority (27, 67.5%) waited for self recovery, 21 (52.5%) had lack of money, 5 (12.5%) did not receive any advice to receive treatment. Four (10%) respondents said that the health care facility was too far to receive treatment and 3 (7.5%) respondents did not feel that treatment was necessary. [Health seeking behaviour of the mothers / care givers was statistically highly significant in educated person. They took the child to Govt. hospital (p=0.001) during illness. The relationship between health seeking behaviour and monthly family income of the respondents was statistically significant. The respondents took their child to medical college hospital (p=0.040) and also consulted drug sellers (p=0.038) during illness of the child.] Conclusion: Health education and behaviour change communication activities can be undertaken in the slum for mothers / care givers about early recognition of childhood illness and on the importance of seeking early treatment. Pulse Vol.7 January-December 2014 p.5-15